A case-report of two patients with hereditary protein S deficiency treated by rivaroxaban. Issue 6 (August 2020) - Lou, Jianyao; Yin, Li; Ke, Xueying; Zhang, Liang; Xu, Fangfang; Liu, Zhenjie
Abstract : N/A: Hereditary protein S deficiency is an autosomal dominant disorder associated with a high risk of venous thromboembolism (VTE) and usually results from mutations of PROS1 . Historically heparin and warfarin have been applied as recommended treatment of VTE. Recent researches showed that rivaroxaban provided more consistent and predictable anticoagulation than warfarin. However, it is unknown whether rivaroxaban is effective for the treatment of VTE in patients with thrombophilia, including protein S deficiency, due to lack of evidence. Here, we report two cases of recurrent VTE in two patients with hereditary protein S deficiency, owing to the same nonsense mutation in PROS1, which were successfully treated by rivaroxaban monotherapy.